IEEE Sensors, 2005.
DOI: 10.1109/icsens.2005.1597627
|View full text |Cite
|
Sign up to set email alerts
|

A Wireless Implantable Passive Strain Sensor System

Abstract: A design study of a novel passive strain-sensor technology for the in-situ measurement of small strains on implants, bones or fixation systems is presented. The sensing principle is based on hydro-mechanical strain amplification which allows for the abandonment of any electrical circuits. Thus, the sensor can be fabricated applying solely biocompatible or bioresorbable polymeric materials. Finite element simulations are employed to validate the basic sensing principle and to optimize design parameters accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Certain sensing environments benefit from, if not require, a wireless sensor embodiment. For instance, wireless strain sensors have been demonstrated for medical applications to monitor human biological factors, thus avoiding invasive wired techniques [1]- [3]. Interest has also been expressed for structural health monitoring (SHM) applications where wired strain sensors cannot be used due to moving parts or where wire weight and routing are a concern [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Certain sensing environments benefit from, if not require, a wireless sensor embodiment. For instance, wireless strain sensors have been demonstrated for medical applications to monitor human biological factors, thus avoiding invasive wired techniques [1]- [3]. Interest has also been expressed for structural health monitoring (SHM) applications where wired strain sensors cannot be used due to moving parts or where wire weight and routing are a concern [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…A large body of research has been demonstrated on various biomedical applications of sensors, but most efforts have focused on clinical monitoring rather than TE/RM or preclinical applications [80,81]. Implantable sensors differ significantly in their designs and fabrication techniques, but the endpoint sensing modalities include biopotential [82], electrical impedance [83], pressure [84,85], flow [86,87], strain [88], oxygen [89], pH [83], and glucose [90,91].…”
Section: Implantable Sensors Applications In Te/rmmentioning
confidence: 99%
“…Assuming that k is upper bounded by N , which is the case for finite capacity channels, then Equation (9) represents N equations in P k f , β, and together with the constraint in Equation (10) (9) on Equation (3) and simplifying 1 , we get:…”
Section: Optimal Detector Designmentioning
confidence: 99%
“…An example of a passive wireless sensor for measuring temperature, stress, strain, acceleration and displacement using Surface Acoustic Wave (SAW) transducer is described in [8]. In the health care domain, a passive strainsensor technology for the measurement of small strains on bones or fixation systems in the human body is presented in [9]. In the automotive industry, passive wireless strain monitoring of car tires is described in [10].…”
Section: Introductionmentioning
confidence: 99%